Cohort profile: The Malaysian Cohort (TMC) project: a prospective study of non-communicable diseases in a multi-ethnic population - Jamal, Rahman; Syed Zakaria, Syed Zulkifli; Kamaruddin, Mohd Arman; Abd Jalal, Nazihah; Ismail, Norliza; Mohd Kamil, Norkhamiwati; Abdullah, Noraidatulakma; Baharudin, Norhafizah; Hussin, Noor Hamidah; Othman, Hanita; Mahadi, Nor Muhammad; Mamat,, Nik Mazlan (Oxford University Press on behalf of the International Epidemiological Association, 2015)
The Malaysian Cohort study was initiated in 2005 by the Malaysian government. The topdown approach to this population-based cohort study ensured the allocation of sufficient funding for the project which aimed to recruit 100 000 individuals aged 35–70 years. Participants were recruited from rural and urban areas as well as from various socioeconomic groups. The main objectives of the study were to identify risk factors, to study gene-environment interaction and to discover biomarkers for the early detection of cancers and other diseases. At recruitment, a questionnaire-based interview was conducted, biophysical measurements were performed and biospecimens were collected, processed and stored. Baseline investigations included fasting blood sugar, fasting lipid profile, renal profile and full blood count. From April 2006 to the end of September 2012 we recruited a total of 106 527participants. The baseline prevalence data showed 16.6% participants with diabetes, 46.5% with hypertension, 44.9% with hypercholesterolaemia and 17.7% with obesity. The follow-up phase commenced in June 2013. This is the most comprehensive and biggest cohort study in Malaysia, and has become a valuable resource for epidemiological and biological research. For information on collaboration and also data access, investigators can contact the project leader at (rahmanj@ppukm.ukm.edu.my).